Fictional Modalities in "Turkish Realistic Folk Tales from the Republic of Macedonia" by Sevim Pilichkova - Trajce Stameski (VERMILION International Journal of Literature and Art, 2018)
In the book Turkish Realistic Folk Stories from the Republic of Macedoniacreated as a result of a twenty-year field research, the collector, editor and proofreader Sevim Pilichkova points out to a thematic wide repertoire of Turkish realistic folk tales which speaks to the great popularity of these narratives among the narrators -Turks from the Republic of Macedonia.
Keywords: Folklore, modalities, narratives, realistic folk tales